How Wealthy is Mozambique after the Discovery of Coal and Gas? Measuring Wealth in Mozambique Using the Wealth Accounting Framework - Armas, Enrique Blanco (World Bank, Washington, DC, 2014)
The objective of this policy note is to inform policy discussions around the management of natural resources and reforms needed to translate natural capital into other forms of capital, and it does so by using the wealth accounting framework. Wealth (e.g. in the form of natural resources) may or may not translate into sustained flows of income in the long run. The extent to which natural capital translates into other forms of capital from which to derive a sustainable income stream is what lies at the heart of natural resources management and what differentiates successful natural resource rich countries from less successful ones. The outcome of the process depends on institutional capacity and political decisions along the way. Experience shows that the quality of governance and institutional capability are a key for countries to be able to translate natural capital into other forms of capital in an effective way. According to a variety of governance indicators, Mozambique's institutions are relatively weak, raising concerns about the country's ability to manage natural resources well. But Mozambique can also build on significant progress in some areas. Democratic elections, free press and a vocal civil society suggest of a gradual strengthening of institutions. Although the main audience of this policy note is Mozambican policy makers - the discussion around management of natural resources needs to be much broader, and as such civil society, private sector and the international community may also find the note useful.